TRENDS IN WEB BASED LEARNING ISSUES IN MATHEMATICS EDUCATION: A BIBLIOMETRIC ANALYSIS - Stevi Natalia (International Journal of Teaching and Learning, 2023)
This paper aims to provide an overview of trend issues regarding writings related to web-based learning (WBL) in the scope of mathematics education. This paper comes from 51 writings taken from the Scopus data base for the last 10 years, namely 2013-2023. The method used is bibliometric analysis using the help of Vosviewer and Mendeley. Based on the results of this paper study, it was found that writing about WBL in mathematics education is still low. There were 26 participating countries but the largest country, the United States, only produced 13 writings. In addition, collaboration between countries is still very low. Not only the linkage between countries, the relationship between keywords and WBL in mathematics education is also still few and tenuous. The keywords that are rarely used in writing related to web- based learning are about problem-based learning, high school, academic achievement, course design, flipped classroom, personalized learning, Moodle creativity, which are things that are closely related to learning approaches or methods. This is expected to be an opportunity and challenge in building novelty in future research.